2012
DOI: 10.3109/00016357.2012.696686
|View full text |Cite
|
Sign up to set email alerts
|

Durability of bond between an indirect composite veneering material and zirconium dioxide ceramics

Abstract: Application of a combination of hydrophobic phosphate monomer (MDP) and initiator results in a durable long-term bond between Katana zirconia and Estenia C&B composite material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…2 and 7B). The present findings can be explained by two factors: (1) bonding to a zirconia surface primed with phosphate monomer (a phosphate monomer improves bond durability between an indirect composite material and a zirconia framework) 17,28) , and (2) bonding to a silica layer treated with silane (3-TMSPMA) (the silane forms strong chemical bonds through a siloxane bond with embedded silica on the zirconia surface) 34,35) . Furthermore, it can be presumed that the acid functional phosphate monomer enhances formation of siloxane bonds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 and 7B). The present findings can be explained by two factors: (1) bonding to a zirconia surface primed with phosphate monomer (a phosphate monomer improves bond durability between an indirect composite material and a zirconia framework) 17,28) , and (2) bonding to a silica layer treated with silane (3-TMSPMA) (the silane forms strong chemical bonds through a siloxane bond with embedded silica on the zirconia surface) 34,35) . Furthermore, it can be presumed that the acid functional phosphate monomer enhances formation of siloxane bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that the shear bond strength of indirect composite materials to zirconia frameworks was greater than 20 MPa 15,17) , which is above the threshold for clinically acceptable composite-metal and compositeceramic bonds 19,20) . Application of a combination of hydrophobic phosphate monomer (MDP) and initiator provided durable bonding between airborne-particleabraded zirconia and indirect composite material 15,17) . Fushiki et al 16) demonstrated that the use of a silane coupling agent and opaque material yielded stable bond strength of the indirect composite and feldspathicporcelain-coated zirconia, and suggested that feldspathic porcelain coating of zirconia frameworks was an effective method to achieve clinically acceptable bond strengths.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics of composite materials could improve the functional aspects of restorations, especially under conditions of high occlusal stress, such as those associated with implantsupported fixed restorations 10) . In vitro studies of bond performance between indirect composite materials and zirconia ceramics for zirconia-based composite-veneered restorations found that application of a hydrophobic phosphate monomer (MDP)/initiator combination resulted in satisfactory initial and durable bond strength between the two materials 14,15) . One study evaluated the fracture resistance of implant-supported, single-tooth, zirconiabased composite-layered molar restorations 16) , which have a potential fracture resistance comparable to that of porcelain-fused-to-metal and zirconia-based all-ceramic restorations.…”
Section: Introductionmentioning
confidence: 99%